The Effect of Colony Addition of Bees (Apis cerana and Tetragonula laeviceps) in Pollination and Fruit Set of Pummelo (Citrus maxima (Burm.) Merr.) - Anisa, Henta Ria; Atmowidi, Tri; Priawandiputra, Windra; Kahono, Sih (HAYATI Journal of Biosciences, 2025)
Pummelo (Citrus maxima (Burm.) Merr.) (Rutaceae) is a cultivated species with a high economic value and several cultivars are found in Indonesia. Bageng Taji is a seedless pummelo cultivar found in Bageng village, Pati regency, Central Java, Indonesia. This research aims to measure the effect of colony addition of two bee species, Apis cerana and Tetragonula laeviceps in pollination and fruit set of pummelo. We set-up four treatments of pollination, i.e., bagged flowers (control), open flowers , colony addition of A. cerana (honey bee), and colony addition of T. laeviceps (stingless bee). Visiting activity of bees were observed by using focal sampling method in the sunny days. Pollen load was measured using the acetolysis method. The effectiveness pummelo pollination was measured based on fruit formations. Results showed that the longest visitation and the number of flowers visited of A. cerana (15.2 seconds/flower and 37.3 flowers/5 minutes) and T. laeviceps (45.5 seconds/flower and 17.1 flowers/5 minutes) occurred at 09.30 am. The average number of pollens carried by A. cerana (19,908 pollen grains) was higher than T. laeviceps (4,308 pollen grains). Addition of A. cerana and T. laeviceps colonies increased 34% and 32% of fruit formation compared to control plants.